Intelligent hydrogels for cartilage regeneration - Castilho, Diogo António Prudente Marques de (2022)
Osteoarthritis (OA) is a frequent degenerative condition of the articular cartilage characterized by hypertrophic changes in the bone. It is the most typical joint disorder, affecting approximately 300 million worldwide. Due to this and the lack of cartilage’s healing capabilities, many studies have been conducted to find a cure for OA. Several clinical procedures with the aim to reduce the pain or lack of movement have already been applied in patients with OA, and even though the results seem promising in the early post-operatory, they are never permanent. Novel techniques for cartilage regeneration have been studied, including using natural polymer-based hydrogels, since natural polymers have many different and unique properties advantageous for cartilage regeneration. Chitosan (CHI) is the most promising biopolymer for the treatment of OA since it is biocompatible, biodegradable, and composed of D-glucosamine units. This monomer is a natural building block of the cartilage and plays a massive role in its regeneration, being responsible for attenuating inflammation, inhibiting the activity of different enzymes responsible for cartilage degradation and repairing damaged tissues. Therefore, the work developed in this master's thesis aims to prepare a CHI hydrogel that promotes cartilage regeneration, by attenuating inflammation, from the phased release of D-glucosamine units by the action of encapsulated enzymes. Methacrylated low molecular weight CHI (LmwMACHI) with 22% modification degree was obtained by modification of CHI with methacrylic anhydride. LmwMACHI can form hydrogels through covalent bonds between its methacrylic groups when exposed to UV irradiation. Mechanical characterization evidenced that Double-Network (DN) hydrogels presented better results than LmwMACHI hydrogels, in Young’s modulus and toughness, and the same happened with the 2% MACHI DNWTPP 50/50 hydrogels. Exo-β-D-glucosaminidase and α-amylase were chosen, out of a group of tested enzymes, to be encapsulated in a 2% MACHI DNWTPP 50/50 hydrogel and demonstrated a phased release of D-glucosamine monomers. To evaluate the anti-inflammatory effect, biological assays of in vitro cell culture were performed using the hydrogel 2% MACHI DNWTPP 50/50 with the encapsulated enzymes. The results indicated that the amount of D-glucosamine released by the hydrogels was not effective in preventing inflammation. To conclude, the developed hydrogels are promising, but lack optimization in the release of D-glucosamine.